WHISTLE BLOWING POLICY AND THE FIGHT AGAINST CORRUPTION: IMPLICATIONS FOR SOCIO-ECONOMIC DEVELOPMENT IN NIGERIA - Awogu, Charles Olisa; Obilor, Ngozi Mary; Maduagwuna, Raymond Emeka (African Journal of Social and Behavioural Sciences, 2021)
This study investigated the impact of the whistle-blowing policy on corruption and the extent to which this has affected Nigeria‟s development. While whistleblowers are not encouraged to blow the whistle, the money recovered from looters seems not to have been properly accounted for or reinvested into the country. Thus, this study tried to answer three research questions. The routine activity theory was adopted for this study because; it effectively explains the adoption of the whistle blowing policy as a mechanism to combat crime in Nigeria. The data for this study was collected through the use of internet materials, textbooks, journals and key person interviews. Four key persons were interviewed from the Independent Corrupt Practices Commission (ICPC) and one from the Ministry of Finance. All respondents were within level 10 to 20 of the civil service. Findings revealed that the whistle-blowing policy was an effective tool in the fight against corruption but, it has not affected the development of Nigeria positively because the money recovered from loots are not reinvested into the economy. It was also found out that low submission of tips and lack of fund for proper investigation of corruption cases are the major challenges which the programme suffers. Therefore, it was recommended that those who give information that leads to the recovery of loots be given incentives. It was also recommended that loots be accounted for properly and reinvested into Nigeria‟s economy to enhance socio-economic development.